Virological and immunological efficacy of metabolically favorable antiretroviral therapy regimens in HIV patients who had no previous treatment - E. I. Veselova; K. A. Kocharyan; O. V. Lovacheva; G. D. Kaminskiy; A. G. Samoylova; I. A. Vasilyeva (Туберкулез и болезни лёгких)
The objective: to study efficacy and safety of metabolically favorable antiretroviral therapy regimens (ART), their effect on HIV RNA levels, levels of CD4, CD8 T lymphocytes, and the ratio of CD4/CD8 in HIV patients who had no previous treatment.Subjects and methods. The study included 80 patients with HIV infection who no received ART previously, 67 of them – without clinical manifestations of HIV infection, 13 – with HIV associated diseases. The virological and immunological efficacy of three ART regimens was evaluated: rilpivirine + emtricitabine + tenofovir (RPV + FTC + TDF); dolutegravir, emtricitabine, tenofovir (DTG, FTC, TDF); raltegravir, etravirine, lamivudine (RAL, ETR, 3TC) during the first 6 months of treatment.Results. By the end of the 6th month of ART, the rate of decrease of viral load compared to the initial level increased in the series RPV + FTS + TDF < RAL, ETR, 3TC < DTG, FTC, TDF. The number of CD4 T-lymphocytes and the ratio of CD4/CD8 increased in all three ART regimens; the number of CD8 T-lymphocytes varied depending on the treatment regimen, the presence or absence of clinical manifestations. The assessment of ART efficacy should be based on the clinical signs of HIV infection. To assess treatment efficacy, it is necessary to control the viral load and three immunological parameters: the number of CD4, CD8 T-lymphocytes, and the ratio of CD4/CD8.